Mechanics of Structural Elements Theory and Applications - Slivker, Vladimir (Foundations of Engineering Mechanics, 2007)
The book systematically presents variational principles and methods of analysis for applied elasticity and structural mechanics. The variational approach is used consistently for both, constructing numerical procedures and deriving basic governing equations of applied mechanics of solids; it is the derivation of equations where this approach is most powerful and best grounded by mathematics. The book is oriented towards experts in civil engineering, researchers, developers of software for mechanical strength, stability, and oscillation analysis; it can be used by practical engineers who employ software tools to do their job and who want to know more about the theoretical background of the strength analysis. The book will be useful to senior and postgraduate students of engineering, to professors of structural analysis at civil or mechanical engineering departments of technical universities.